The Use of Clustering Model to Improve Poetry Writing Skills of SMP Negeri 4 Watampone, Bone Regency, Indonesia - Safar, Muh.; Andi Srimularahamah; Arif Rahman Aulia Jamnawi; Fahri Akbar (Enigma Institute, 2023)
This research aims to describe the improvement of writing skills of students in class VIII B SMP Negeri 4 Watampone, Bone Regency through the use of clustering model. This research was conducted by pre-observation in class VIII B. The writing skills of students of class VIII B SMP Negeri 4 Watampone are still low or lacking. The targets to be given action are students of class VIII B SMP Negeri 4 Watampone in 2022/2023 academic year. This research is classroom action research. The research procedure was carried out in 2 (two) cycles and each cycle had 3 meetings. Each cycle consists of four stages, namely: planning, action implementation, observation, and reflection. The techniques of data collection in this classroom action research are observation, documents, student assignments and tests. The data analysis was conducted using qualitative and quantitative techniques. The criteria for success of classroom action is the test of writing poetry using the clustering model. The use of clustering models in learning to write poetry can improve the quality of the process and students’ learning outcomes. It shows that there is an improvement in the completeness of the ability to write poetry from pre-cycle as many as 12 or 36.4%, cycle 1 as many as 21 or 63.6% and cycle 2 as many as 33 or 100%. Based on the improvement in student learning completeness in each cycle, the use of the clustering model needs to be applied to the learning of writing poetry of students in class VIII B SMP Negeri 4 Watampone, Bone Regency.